The construction of nationhood : ethnicity, religion, and nationalism - Hastings, Adrian (Wiles lectures, 1997)
Hastings presents a thorough re-analysis of nationalism and nations which challenges the current 'modernist' orthodoxies. The development of the nation-state is seen as central to the subject but the analysis includes many other examples.